The Influence of Academic Self-Efficacy, Academic Resilience, and Academic Self-Regulation on Learning Outcomes in Service, Trading, and Manufacturing Companies Accounting : (Case Study Of 11th-Grade Students Of The Accounting And Institutional Finance Program At A State Vocational School In Central Jakarta) - Diva Surya Aprilia; Erika Takidah; Sri Zulaihati (RTTM, 2025)
This study aims to examine the influence of academic self-efficacy, academic resilience, and academic self-regulation on students’ learning outcomes in the subject of Service, Trading, and Manufacturing Company Accounting. A quantitative survey method was applied to a sample of 140 11th-grade Accounting and Finance students from three vocational high schools in Central Jakarta, selected using proportional stratified random sampling. Data were collected through a closed-ended questionnaire and analyzed using multiple linear regression. The results show that academic self-efficacy, academic resilience, and academic self-regulation significantly and simultaneously affect students’ learning outcomes (F = 167.325; p < 0.001). Partially, all three variables also show a positive and significant effect. The coefficient of determination (R² = 78.7%) indicates that these internal psychological factors substantially influence academic performance. These findings highlight the importance of psychological development in enhancing academic achievement. It is recommended that teachers and schools provide more support in fostering students’ self-confidence, academic persistence, and learning regulation skills.